Rancang Bangun Simulator Sinkronisasi Generator Sinkron 3 Fasa Semiotomatis Berbasis Mikrokontroler Arduino - Suharno, Dedi Nono; Iwan Setiawan (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2020)
A large supply of electrical power at industry is obtained from generators and PLN which can be operated alternately or together in parallel to supply power to loads either manually or automatically. This condition is for economic reasons and maintenance purposes. In parallel process of a generator, requirements are needed, the frequency, voltage and phase sequence must be the same. For parallel processing, a device called a synchronoscope is needed. In this research, a three-phase synchronous generator synchronoscope simulator that works in parallel with the PLN source semi-automatic using an Arduino microcontroller is made. The synchronoscope simulator works semi-automatically because the voltage and frequency settings of the synchronous generator are not manual. To detect the synchronization parameters of a three-phase synchronous generator, sensors and controllers are made. The components are ZMPT101B voltage sensor, PC817 optocoupler frequency sensor, phase sequence sensor and Arduino Mega 2560. The purpose of this research is to design and create a three-phase generator synchronization simulator based on the Arduino microcontroller which can be synchronized with a maximum of 15 seconds with a measurement error below 5%. The result is that the maximum synchronization process time is 11 seconds and the measurement error is 4.5%.